Metode Triangulasi Dalam Penelitian Ilmu Komunikasi - Wiryanto, Wiryanto (Universitas Prof. Dr. Moestopo (Beragama), 2006)
AbstractTriangulation is the application and combination of several research methodologies in the study of the same phenomenon. It can be employed in both quantitative(validation) and qualitative(inquiry) studies, a method-appropriate strategy of founding the credibility of qualitative analyses, becomes an alternative to